Determination of DNA Damage Caused by Food Additives Using Comet Assay Method : Food Additives DNA damage via comet assay - Dosay-Akbulut, Mine (Progress in Nutrition, 2021)
Additives have been used to improve specific characteristics of food products. As a result of the rapid increase in the use of chemical substances such as food additives in every area, it has become very important to determine whether these chemicals have negative effects on the genetic structure of living things. Food additives are substances and used to preserve flavor or enhance its taste, appearance, or other qualities of foods. Especially; food preservatives within food additives are in use to protect the food against to microorganisms negative effect. The risk assessing from food additives to human health carried out by WHO, in cooperation with FAO. However, the increased consumption of food additives may result to toxic reactions. It was indicated by different studies that some food additives have genotoxic and carcinogenic effects in different test organisms including plants, bacteria, human lymphocytes and in different organs, mice and rats. The effects of genotoxic and cytotoxic agents on living cells can be determined bu using comet assay anaysis. In recent years, the comet assay method has been widely preferred because of its advantageous, precise and fast results. Becasue of being carcinogenics possibility it should be more concious and be more carefull in taking food additives to our life.